Sex differences in plasma and liver lipid peroxide and liver glutathione levels in Wistar rats - (:unkn) unknown (My University, 2000)
Normal levels of plasma and liver lipid peroxides in male and female rats were compared and it was seen that there were no significant differences. Normal levels of liver glutathione in females were lower than males.
Keywords: Glutathione; Lipid peroxidation; Sex difference